Etica applicata, ambiente, paesaggio - Morandini, Simone (Ri-Vista. Research for landscape architecture, 2015)
Ethics applied to environment and landscape is a topic that has a wide range of approaches. The shared acknowledgement of environment as a value, is not enough to guarantee clear indications about how to inhabit it. Just a few words, to which the human experience assigned a key role in evaluating the correctness of our acts, guide us : solidarity, justice, quality of life, responsibility.